Microneedle Array-Assisted, Direct Delivery of Genome-Editing Proteins Into Plant Tissue - Viswan, Anchu; Yamagishi, Ayana; Hoshi, Masamichi; Furuhata, Yuichi; Kato, Yoshio; Makimoto, Natsumi; Takeshita, Toshihiro; Kobayashi, Takeshi; Iwata, Futoshi; Kimura, Mitsuhiro; Yoshizumi, Takeshi; Nakamura, Chikashi (Frontiers in Plant Science, 2022)
Genome editing in plants employing recombinant DNA often results in the incorporation of foreign DNA into the host genome. The direct delivery of gene-editing proteins into plant tissues is desired to prevent undesirable genetic alterations. However, in most currently available methods, the point of entry of the genome-editing proteins cannot be controlled and time-consuming processes are required to select the successfully transferred samples. To overcome these limitations, we considered a novel microneedle array (MNA)-based delivery system, in which the needles are horizontally aligned from the substrate surface, giving it a comb-like configuration. We aimed to deliver genome-editing proteins directly into the inner layers of leaf tissues palisade and the spongy and subepidermal L2 layers of the shoot apical meristem (SAM) which include cells that can differentiate into germlines. The array with needles 2 µm wide and 60 µm long was effective in inserting into Arabidopsis thaliana leaves and Glycine max (L.) Merr. (soybeans) SAM without the needles buckling or breaking. The setup was initially tested for the delivery of Cre recombinase into the leaves of the reporter plant A. thaliana by quantifying the GUS (β-glucuronidase) expression that occurred by the recombination of the loxP sites. We observed GUS expression at every insertion. Additionally, direct delivery of Cas9/sgRNA targeting the PDS11/18 gene in soybean SAM showed an 11 bp deletion in the Cas9/sgRNA target site. Therefore, this method effectively delivered genome-editing proteins into plant tissues with precise control over the point of entry.